Record of the Amarsipa fish (Family Amarsipidae) from Pratas Island, South China Sea - Ho, Hsuan-Ching; Su, Yo; Lin, Chien-Hsiang; Chu, Tah-Wei (Zootaxa, 2023)
Two specimens of the rare Amarsipa fish, Amarsipus carlsbergi, were collected from Pratas Island in the northern South China Sea. They represent the first record of Taiwanese EEZ and fill the distribution gap in the northwestern Pacific Ocean between Japan (East China Sea) and Vietnam. The two specimens were identified based on their diagnostic characteristics, including no pharyngeal sacs, a pelvic fin well in front of the pectoral fin, a slender body and other morphology. Detailed data and descriptions of these two specimens, including a description of otolith morphology, are provided.